Hazard Analysis Critical Control Points (HACCP) Principle 5: Establish Corrective Actions - Ronald H. Schmidt; Debby Newslow (EDIS)
FSHN07-06, a 7-page fact sheet by Ronald H. Schmidt and Debby Newslow, explains the necessary steps in a HACCP system for taking a corrective action once a food safety hazard has been discovered. Published by the UF Department of Food Science and Human Nutrition, July 2007.